Antibacterial Effect of Combinations of Salvia officinalis and Glycyrrhiza glabra Hydroalcoholic Extracts against Enterococcus spp. - Santos, Thaís da Silva Alves [UNESP]; Meccatti, Vanessa Marques [UNESP]; Pereira, Thaís Cristine [UNESP]; Marcucci, Maria Cristina [UNESP]; Hasna, Amjad Abu [UNESP]; Valera, Marcia Carneiro [UNESP]; de Oliveira, Luciane Dias [UNESP]; Carvalho, Cláudio Antonio Talge [UNESP] (MDPI, 2023)
Enterococcus spp. are a common culprit behind the failure of endodontic treatments, primarily due to their notorious resistance to antimicrobial agents. Considering this challenge, this study was conducted to assess the antimicrobial efficacy of a unique blend of hydroalcoholic extracts sourced from Salvia officinalis and Glycyrrhiza glabra against biofilms formed by Enterococcus faecalis and Enterococcus faecium. The chemical composition of these plant extracts was rigorously characterized, with primary compound quantification achieved through high-performance liquid chromatography (HPLC-DAD) analysis. Additionally, this study determined the minimal bactericidal concentrations of these extracts and evaluated their potential to combat biofilms by quantifying colony-forming units per milliliter (CFU/mL). The findings reveal that the simultaneous application of both extracts yielded additive and synergistic effects against E. faecalis and E. faecium, including both ATCC and clinical strains. Impressively, after a 24 h exposure, these extract combinations demonstrated efficacy comparable to that of a 0.12% chlorhexidine solution, establishing a statistically significant difference from the negative control group. Consequently, the concurrent use of these extracts emerges as a promising alternative antimicrobial strategy for addressing Enterococcus spp. in endodontic treatments, holding substantial potential for clinical applications in this context.
Keywords: anti-bacterial agents; Enterococcus faecalis; Enterococcus faecium; Glycyrrhiza glabra; Salvia officinalis